NIVAQUIN SONTOQUIN IN THE TREATMENT OF GIARDIASIS - SOBERON, G; PELAEZ, DIONISIO; PARRA, GALO (Universidad Nacional Autónoma de Mexico, Instituto de Biología, CD MEXICO, DF, MEX, 1976)
The yeasts were isolated from various drinks prepared in the area; the other collections were made from gardens and slopes In all, 16 strains of yeasts were studied, while 17 genera of macroscopic fungi (5 families), 14 genera of lichens (10 families) an
CIENC MEX
Keywords: NIVAQUIN, SONTOQUIN, TREATMENT, GIARDIASIS; CIENCIAS MEDICAS; CIENCIAS CLINICAS; PATOLOGIA CLINICA